Plant Growth Regulators (PGRs) Study for Root and Bud Induction on Stem Cuttings of Stevia rebaudiana - Apriani, Ike; Sonia Adiba; Dawani; Nurseha, Tito; Fatiqin, Awalul; Yessy Velina (Biota, 2024)
The Stevia plant is used as a low calorie natural sweetener known as"the sweet herb of Paraguay". Stevia leaves a higher level of sweetness than cane sugar. Stevia can be propagated by stem cutting techniques. Soaked of stem cuttings in Plant Growth Regulators (PGRs) auxin can promote the growth and development of Stevia. Research was conducted to determine the effect of commercial PGRs (Rootone-f) and natural PGRs from Shallot extract. This study used a complete randomized design with different concentrations, both Rootone-f (0, 100, 200, 300, 400 and 500 mg/L) and shallot extract (0, 0.5%, 1%, 1.5% and 2%). Observations were made after 6 weeks (42 days) of planting on several growth parameters (height of plant, number or buds, number of leaves, number of roots and length of roots). Commercial PGRs showed a significant effect on growth parameters. While natural PGRs of shallot showed a significant effect on height of growth parameters. The recommended concentration of commercial PGRs for Stevia rebaudiana Bertoni M. stem cuttings was 300 mg/L.